Parental Health Education in Identifying Emotional Problems in Children with Autism Spectrum Disorder in Cimahi City SLB (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder characterized by impaired verbal and nonverbal communication, reciprocal social interactions, and restricted and repetitive behavior. Children with ASD tend to have difficulty understanding and expressing emotions, paying attention to facial expressions, other social skills, and emotional skills. As a result, children and parents both do not understand each other. This community service aims to provide understanding to parents in identifying emotional disorders that occur in children, looking for efforts to control children's emotions. This community service method is by conducting outreach by providing health education to parents of children with ASD, which is carried out with lectures and question-and-answer discussions. This socialization was designed using observational analytics with a cross-sectional study design approach. The result of this community service was the presence of parents of Cimahi City SLB students to take part in socialization in efforts to handle emotional problems in children with ASD. It is hoped that parents will be able to identify disorders that occur in children and be able to understand efforts to control children's emotions.